Analysis of the Implementation of Regional Inspectorate Supervision on the Performance of Regional Service Agency Kutai Barat District - Tabita, Martha; Palinggi, Yonathan; Musmuliadi, Musmuliadi (Riviera Publishing, 2022)
Introduction: This study aims to determine the implementation of supervision carried out by the Inspectorate of West Kutai Regency as an internal supervisory agency of the local government on the achievement of the performance of the BKD of West Kutai Regency as a regional staffing institution and what influences the implementation of supervision carried out by the Inspectorate of West Kutai Regency. This research was conducted in West Kutai Regency, with informants of inspectorate and BKD employees who were considered competent. Data was collected through field observations and in-depth interviews. Methods: This research method is descriptive and qualitative. Results: The results of the study show that the implementation of supervision carried out by the Inspectorate of West Kutai Regency on BKD through three stages, namely: First, the preparation of supervision carried out by inspectorate officials. . Second, the implementation of supervision carried out by inspectorate officials, the author considers that what is done by inspectorate officials has not been effective. Third, the implementation of the preparation and accountability of the audited SKPD reports, in this case, the BKD, has not been supported by the availability of accurate/valid data to be presented. Conclusion: The factors that influence the implementation of the inspectorate's supervision on the performance of the Regional Personnel Board of West Kutai Regency are: (1) Internal and (2) External factors.